USE OF WEB 2.0 TOOLS BY POLISH HEALTH PORTALS - Czerwinska, Magdalena (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2020)
The Internet, as a global, universal communication network, has become an important channel of information distribution. Currently, it has a very social character, thanks to the dissemination of Web 2.0 sites, which allow users to create and publish their own multimedia content. Web 2.0 technologies make it easier for users to communicate, create, collaborate and share information. They are widely available and are characterized by low costs of use. The article presents the results of research on the most popular Polish health websites. It was examined whether health services meet the requirements of Web 2.0 sites. The analysis is focused on the technological and social aspects. The COVID-19 pandemic lockdown in March and April 2020 in Poland was observed as having an influence on users and views of heath websites. The obtained results confirm the use of elements (both technological and social) by health services selected for research. However the usage of Web 2.0 technologies among websites varies.